Resistant Hypertension From Renal Artery Stenosis Leading to Heart Failure With Preserved Ejection Fraction - Motasem Alyamani MBBS; Jissy Thomas MN, NP; Miriam Shanks MD, PhD; Gavin Y. Oudit MD, PhD (SAGE Publishing, 2018)
Resistant hypertension remains an important cause of heart failure. In this article, we describe a case of resistant hypertension in a 63-year-old woman leading to heart failure and marked morbidity. Her clinical course was characterized by chronic pleural effusions and recurrent hospitalizations with respiratory failure and flash pulmonary edema associated with heart failure with preserved ejection fraction. Her transthoracic echocardiogram showed severe concentric left hypertrophy and diastolic dysfunction. The clinical phenotype was secondary to resistant hypertension due to bilateral renal artery stenosis, and her blood pressure and heart failure resolved after successful renal artery angioplasty. This case demonstrates how heart failure with preserved ejection fraction due to renal artery stenosis can easily go unrecognized especially in patients with multiple comorbidities. The potentially curable nature of this condition clearly warrants consideration especially in patients with multiple risk factors for atherosclerotic vascular disease.